1982
DOI: 10.1139/y82-100
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone and morphine inhibit gastric emptying of solids

Abstract: Gastric emptying studies were performed on six healthy volunteers using a radioisotope test meal. Each subject was studied three times (control, morphine 7.5 mg, naloxone 2 mg). Both intravenous morphine and intravenous naloxone significantly delayed gastric emptying when compared with the control study. These results suggest that opiate receptors, opiate neurones, and enkephalin may regulate gastric motility and that under certain circumstances naloxone may act as an opiate agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
2
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 0 publications
0
13
2
3
Order By: Relevance
“…also reported a small but insignificant delay of gastric emptying given naloxone as bolus injection of 1.2 mg and using the paracetamol absorption test to estimate gastric emptying in eight fasted volunteers. In contrast to our study, Champion et al 18 . demonstrated a significant delay of gastric emptying of a solid meal with naloxone 2 mg bolus injection in six volunteers, also using a scintigraphic method.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…also reported a small but insignificant delay of gastric emptying given naloxone as bolus injection of 1.2 mg and using the paracetamol absorption test to estimate gastric emptying in eight fasted volunteers. In contrast to our study, Champion et al 18 . demonstrated a significant delay of gastric emptying of a solid meal with naloxone 2 mg bolus injection in six volunteers, also using a scintigraphic method.…”
Section: Discussioncontrasting
confidence: 99%
“…demonstrated a significant delay of gastric emptying of a solid meal with naloxone 2 mg bolus injection in six volunteers, also using a scintigraphic method. As it is suggested that naloxone is not a pure opioid receptor antagonist but may also have a weak morphine‐like agonistic effect, they argue that naloxone at this dose (about 2–5 times higher than usually given to reverse narcotic‐induced respiratory depression) may act as a weak opioid agonist instead of an antagonist at lower doses 18,41 . However, using naloxone at a dose of 5 mg bolus injection and a scintigraphic method to estimate gastric emptying time in eight volunteers, Mittal et al 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Der obstipierende Effekt der Opioide ist besonders ftir Morphin [4,38,54,56] demonstriert worden und stellt ein obligates Begleitph~inomen bei der chronischen Therapie von Schinerzpatienten dar [42,49]. Da hierftir ursachlich eine Abnahme der Acetylcholinfreisetzung im Plexus myentericus diskutiert wird [27], k6nnte die obstipierende Wirkung durch spezifische Antagonisten wie beispeilsweise Naloxon aufgehoben werden.…”
Section: Diskussionunclassified
“…So ist aus der klinischen Anwendung bekannt, dab die chronische Einnahme von Opioiden bei Schmerzpatienten in fast 95 % aller F~ille zur Obstipa-ti0n ftihrt [5], die so ausgepr/igt sein kann, dab routinem/ii]ig mit dem Opioid Laxanzien verordnet werden miissen [16]. Urs~ichlich liegt dieser obstipierenden Wirkung eine Pyloruskonstriktion mit verz6gerter Magenentleerung [4], eine Hemmung der propulsiven Motorik sowie eine spastische Einschntirung des Dtinndarms zugrunde [27]. Dieser Wirkmechanismus wird dann verst/indlich, wenn man berticksichtigt, dab 0pioide an spezifische Rezeptoren im Plexus myentericus binden, wodurch die Freisetzung von Acetylcholin verhindert wird [11,27].…”
unclassified
“…Dies leuchtet unmittelbar ein, wenn man bedenkt, daß die oroanale Transitzeit zu über 90% auf der Kolontransitzeit beruht [5].…”
unclassified